ANALISIS EFEKTIVITAS ALOKASI DANA DESA (ADD) DALAM MENUNJANG PEMBANGUNAN PEDESAAN DI DESA MUKAI MUDIK KECAMATAN SIULAK MUKAI KABUPATEN KERINCI TAHUN 2010-2017 - Mira Hastin; Defti Gia Putri (Jurnal Akrab Juara, 2019)
The purpose of this study was to find out and describe how effective the Village Fund Allocation (ADD) was in supporting rural development in the Mukai Mudik Village, Siinci District, Kerinci District, 2010-2017. The research method used is quantitative and qualitative descriptive. The type of data used is secondary data. The results showed that the average effectiveness of Village Fund Allocation in Mukai Mudik Village from 2010 to 2017 was effective, because the realization percentage was 90.2%. This indicates that the management of Village Fund Allocation in Mukai Mudik Village has not been optimally implemented. Because the realization of the Village Fund Allocation obtained has not yet reached the revenue target set in the Village Fund Allocation budget.